Price discrimination against retail Investors: Evidence from mini options - Li, Yubin; Zhao, Chen; Zhong, Zhaodong (Journal of Banking & Finance, 2019)
This paper studies the rise and fall of “Mini” options that are especially catered to retail investors for popular but high-priced securities. Using transaction-level data, we find that transaction costs of Mini options are much higher than those of standard options and the difference cannot be fully explained by cost-related determinants. Furthermore, we find evidence of price discrimination against retail investors from analyses of price elasticities of option traders, an event-study of changes in bid-ask spreads around earnings announcements, and comparisons of trade prices paid by Mini and standard option traders for the same security at approximately the same time.